1998
DOI: 10.1111/j.1399-0039.1998.tb02971.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II allele and haplotype frequencies in Ethiopian Amhara and Oromo populations

Abstract: Acknowledgments:We would like to thank J. Clayton for his help in statistical analysis, M. T. Senegas and E. Guitard for DNA collection management and I. Rouch and M. L. Abstract: HLA class II alleles were idenfied in 181 healthy unrelated Ethiopian children of both sexes and in 350 European controls from the South of France. The Ethiopian individuals belonged to the two major ethnic groups of the country: Oromo (N=83) and Amhara (N=98). In both panels, genetic polymorphism of HLA class II alleles was analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…The present study and a previous one [29] also showed that the frequencies of HLA-DQB1*02 (a risk allele for podoconiosis) and HLA-DRB1*13 (a protective allele against podoconiosis) in the Ethiopian population were among the highest in Sub-Saharan Africa. HLA-DQB1*02 had the third highest frequency in the Ethiopian ethnic groups following Burkina Faso’s Fulani (DQB1*0201, 36.0%) and Central African Republic’s Aka Pygmy group (DQB1*0201, 36.9%).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The present study and a previous one [29] also showed that the frequencies of HLA-DQB1*02 (a risk allele for podoconiosis) and HLA-DRB1*13 (a protective allele against podoconiosis) in the Ethiopian population were among the highest in Sub-Saharan Africa. HLA-DQB1*02 had the third highest frequency in the Ethiopian ethnic groups following Burkina Faso’s Fulani (DQB1*0201, 36.0%) and Central African Republic’s Aka Pygmy group (DQB1*0201, 36.9%).…”
Section: Discussionsupporting
confidence: 85%
“…Finally, we compared HLA allele frequency distributions between the population group in our dataset and unrelated and apparently healthy children of Oromo (n = 83) and Amhara (n = 98) ethnicity from central Ethiopia (http://www.allelefrequencies.net/). The mean age of the Oromo and Amhara subjects was 8.2 years, and ranges between 4 and 12 years [29], [44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent three‐locus haplotype DRB1*0701‐DQA1*0201‐DQB1*0201 (~13%) of north Indian Hindus was found in all the Caucasian populations ranging from 4.90% in Greeks (Fort et al ., 1998) to 20.1% among US Caucasians (Sanchez‐Velasco et al ., 2003). However, this haplotype cannot be defined as a true Caucasian haplotype as various African populations like Ethiopians Amharas — 19.20% (Fort et al ., 1998), Algerians — 9.9% (Djoulah et al ., 1994) and Moroccans — 20% (Gomez‐Casado et al ., 2000) and populations from East Asia like Chinese (10.20%) have also shown high frequency of this haplotype. We suggest that DRB1*0701‐DQA1*0201‐DQB1*0201 is one of the founder haplotypes and is universally present in all global populations.…”
Section: Discussionmentioning
confidence: 99%
“…To have a broader picture of the genetic relationship between Fulani and other sub-Saharan African populations, we also included in the analysis data retrieved from the HLA Database (frequencies available at www.allelefrequencies.net), including Aka Pygmies from the Central African Republic (CAR) [35], Bantu from the Democratic Republic of Congo (DRC) [35], Banzabi from Gabon [36], Bubi from Equatorial Guinea [37], Amhara and Oromo from Ethiopia [38], Venda from South-Africa [39], and Shona from Zimbabwe [40]. When necessary, correspondent serologic specificities were used, and high-resolution molecular alleles were pooled to allow comparison across the 15 populations, based on current HLA nomenclature [41].…”
Section: Interpopulation Genetic Variationmentioning
confidence: 99%